Extruded-expelled cottonseed meal with lint at a source of rumen undegradable protein for lactating dairy cows - Meyer, M. J.; Shirley, E. C.; Titgemeyer, Evan C.; Scheffel, Michael V.; Park, A. F. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
Twenty-four pluriparous Holstein cows were used in six 4×4 Latin squares to evaluate the value of extruded-expelled cottonseed meal (EECM) with lint as a source of rumen undegradable protein (RUP) for lactating dairy cows. Cows were fed diets typical of those used by commercial dairies with all the cereal grain supplied as corn. Tallow was used to balance the fat level across diets. Experimental diets were: solvent soybean meal (16% CP:35% RUP)=SBM 16-35; solvent soybean meal (18% CP:35% RUP)= SBM 18-35; extruded-expelled cottonseed meal (16% CP:40% RUP)=EC16-40; bloodmeal/ fishmeal (16% CP:40% RUP)=BMFM 16-40. Average milk production was approximately 82 lbs and did not differ among treatments. Cows fed BMFM 16-40 consumed less dry matter than cows fed the other diets and were more efficient in converting feed to milk. No difference was observed in body weight gain among treatments. Percentages of milk fat and protein were similar, but percentage of lactose was less in milk from cows fed BMFM 16-40. Urea nitrogen was highest in milk from cows fed SBM 18-35. Increasing RUP from 35 to 40% of the dietary protein tended to depress dry matter intake with no effect on milk production, whereas efficiency of milk production increased. The casein fraction of milk protein was not affected by diet, but the nonprotein nitrogen fraction was greater in milk from cows fed SBM 18-35. Feed costs/cwt milk were $4.24, $4.29, $3.98 and $5.18 for SBM 16-35, SBM 18-35, EC 16-40, and BMFM 16-40, respectively, based on commodity prices in northeast Kansas. Extruded-expelled cottonseed meal with lint is an acceptable source of rumen undegradable protein for lactating dairy cows.
Keywords: Dairy; Cottonseed meal; Rumen undegradable protein; Lactating cows